Evaluation of the avobenzone photostability in solvents used in cosmetic formulations (2011)
ABSTRACT: The use of sunscreen products is very important nowadays. The photostability of UV filters incorporated in these products must be preserved during its storing and application processes in order to achieve the claims about photoprotection of the commercial products. The photostability of avobenzone, one of the most common UVA filters in commercial sunscreens, is assessed in solvents intended for cosmetic formulations. The study is carried out by following the spectral behavior of avobenzone solutions under irradiation and after storing them in the dark. Different photobehaviors of the avobenzona are found in the selected solvents, some of which can be explained in the same way than in analytical solvents; but for others, the structural and physical properties of the solvents must be taken into account. The most appropriate solvents for ensuring the photostability of avobenzona are mineral oil and isopropyl myristate.